(untitled) (Journal of Global Accounting, 2023)
This study examined the effect of sustainability reporting on the performance of sampled Oil and Gas firms in Nigeria. Performance proxied by return on assets (ROA) was the dependent variable while sustainability reporting surrogated by economic reporting, environmental reporting and social reporting. The major analysis to achieve the specific objectives was performed using the generalized least square (GLS) regression techniques. The significance of the association and relationships was at 5% confidence level. Z-test statistics was used to test the significance of the relationships. The results of the model revealed that the explanatory variables account for as low as 69.51% of the overall variation in the financial performance of sampled Oil and Gas firms in Nigeria. The findings shows that economic reporting and environmental reporting has a significant effect on the financial performance of sampled oil and gas firms in Nigerian while social reporting has no significant effect on the financial performance of sampled Oil and Gas firms in Nigeria. The study recommends among others that, listed oil and companies in Nigeria should intensify economic dimension of sustainability reporting as this could lead to increased performance in addition to satisfying their information needs and assisting them to hold firms to account for not only economic reporting but also environmental and social reporting as its impacts them.